Iroquois Homeodomain transcription factors in ventricular conduction system and arrhythmia - Hu, Wenyu (Int J Med Sci, 2018)
Iroquois homeobox genes, Irx, encode cardiac transcription factors, Irx1-6 in most mammals. These six transcription factors are expressed in different patterns mainly in the ventricular part of the heart. Existing researches show that Irx genes play key roles in the differentiation and development of ventricular conduction system and the establishment and maintenance of gradient expression of potassium channels, Kv4.2. Our main focus of this review is on the recent advances in the discovery of above-mentioned genes and the function of the encoding products, how Irx genes establish ventricular conduction system and regulate ventricular repolarization, how the individual and complementary functions can be verified to complement our cognition and leads to novel therapeutic approaches.